EMPOWERING SMES AND EDUCATORS: A HOLISTIC APPROACH TO TAX AWARENESS AND COMPLIANCE - Khairunnisa, Hera; Musyaffi, Ayatullah Michael; Prihatni, Rida; Rachmadania, Rizki Firdausi; Anugrah, Surya; Suryono, Windy Permata; Sudiati, Rochma; Fhadira, Dinda Marsa; Irawan, Kania Allya; Johari, Razana Juhaida (Yayasan Education and Social Center, 2024)
This program is conducted to increase awareness and tax literacy of SMEs with the hope that SMEs know the taxation process such as calculating, depositing, and reporting. This webinar was held on Wednesday, May 22, 2024 and was attended by 180 participants consisting of SMEs from the East Jakarta and West Jakarta areas, students and lecturers of Universitas Negeri Jakarta, and students of Mara University of Technology Malaysia. Assoc.There were three speakers who filled this webinar event. Prof. Dr. Razana Juhaida Johari as the first speaker explained the concept of accounting for MSMEs, the second speaker, Rizky Tiaro Sulistyo, S.Tr.Ak. delivered material on the Taxation Education Program for MSMEs, Muzaki Andriawan P.S.E., B.K.P., CTAP as the third speaker closed the session with a practical discussion on income tax for MSMEs. The results of this program were carried out well. interesting material for umkm made participants actively ask questions and want to explore more about taxes that apply to umkm and accounting concepts for SMEs.